1983
DOI: 10.1111/j.1476-5381.1983.tb10003.x
|View full text |Cite
|
Sign up to set email alerts
|

Aortic vascular and atrial responses to (±)‐1‐O‐octadecyl‐2‐acetyl‐glyceryl‐3‐phosphorylcholine

Abstract: The effects of (±)‐1‐O‐octadecyl‐2‐acetyl‐glyceryl‐3‐phosphorylcholine (octadecyl‐AGPC) were studied in three types of aortic vascular smooth muscle preparations, namely, strips, rubbed and unrubbed rings, and an atrial preparation in normotensive rats. In the resting tension state, octadecyl‐AGPC did not elicit significant contractions in either rubbed or unrubbed ring preparations at concentrations lower than 1 × 10−4m. However, at a concentration of 3 × 10−4 m, octadecyl‐AGPC markedly contracted both types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The nature of this latter action is unknown. However, there is considerable evidence that Paf, at concentrations relevant to inflammation, does not exert direct effects on vascular and other types ofsmooth muscle (Cervoni et al, 1983;Lefer et al, 1984a). Thus, a further secondary mediator of coronary vasoconstriction may be released by Paf.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of this latter action is unknown. However, there is considerable evidence that Paf, at concentrations relevant to inflammation, does not exert direct effects on vascular and other types ofsmooth muscle (Cervoni et al, 1983;Lefer et al, 1984a). Thus, a further secondary mediator of coronary vasoconstriction may be released by Paf.…”
Section: Discussionmentioning
confidence: 99%
“…A direct stimulation of venular and endothelial cells was suggested. The effect of PAF on microcirculation has been studied also on the hamster cheek pouch (89,119). Vasoconstriction was the predominant vasomotor response to PAF.…”
Section: Microvascular Effect Of Platelet-activating Factor In Vivomentioning
confidence: 99%
“…Levi et al (1984) demonstrated that AGEPC in concentrations of 1O-1-1O-M produced a slight negative inotropic effect in guinea-pig isolated left atria and papillary muscles. On the contrary, a positive inotropic effect of AGEPC at a concentration of l0-4 M in rat atria was reported from two laboratories a (Cervoni et al, 1983;Kamitani et al, 1984). In the light of the present observations, however, these reports may not be contradictory.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the electrophysiological effects of AGEPC might stem from non-specific amphiphile-membrane interaction rather than from activation of specific Paf receptors. It has been also reported that high concentrations (10-'-3 x 10-4 M) ofAGEPC were needed to induce mechanical responses in isolated vascular 40 mV preparations (Cervoni et al, 1983;Kamitani et al, 1984;Vanhoutte & Houston, 1985). Vanhoutte & Houston (1985) have suggested that the Paf-induced | 20 mg relaxation of the isolated coronary artery of the dog is not receptor-mediated, since the mechanical response was not blocked by a Paf-antagonist.…”
Section: Electrophysiological Effects Ofamphiphiles On Guineapigpapilmentioning
confidence: 99%